Student Motivation in Learning Indonesian Language Class VIII - Rahmawati, Rosyadi Nur; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine students' intrinsic and extrinsic learning motiva-tion in grade VIII Indonesian language learning. Methodology: This study uses a qualitative descriptive approach to describe the intrinsic and extrinsic motivations of students. with data sources from questionnaires. Data collection was carried out through observation techniques, question-naires, and documentation. Results: The subject of this study is that the intrinsic motivation of students in lear-ning Indonesian is high by 68%. Meanwhile, extrinsic motivation is high at 82%. Applications/Originality/Value: Based on the results of the research, there are two motivations in learning In-donesian, namely intrinsic motivation and extrinsic motivation.